Gastos com internações hospitalares e sobrevida de pacientes adultos que receberam transplante de fígado no SUS no período 2001-2011 - Eliza Antonia de Queiroz (2016)
The procedures of liver transplants have increased in Brazil as the prevalence of chronic liver diseases are growing in the country. Because there is no alternative treatment for these patients, coupled with the fact that in Brazil 95% of all transplants are funded by the public health system, it is expected significant impact on public expenses. The objective of this study is to estimate the survival of 7,345 adult patients who received liver transplantation and the hospital expenditures of both liver transplant and other hospital care performed during the period 2001-2011 (before or after the liver transplant). This is a pioneering work to incorporate all adult patients who had received liver transplantation in the SUS in a period of eleven years. Data sources are from two administrative data systems of the Brazilian Ministry of Health: the Hospital Information System (SIH/SUS) and Mortality Information System (SIM). The database was structured by applying statistical techniques of probabilistic linkage between these two data sources. The survival curve was estimated by the Kaplan-Meier and a model of Cox proportional hazards was further applied. The costs of transplant procedures, expenditures on other hospital admissions and expenditures per year of survival were calculated. The analysis was performed considering the total of adult patients and by cohorts (defined according to the year of the first liver transplant). According to our results, survival rates were lower than the official rates of the Brazilian Association of Organ Transplantation and those found by national and international empirical studies. The 1-year survival rate was 70.75%. The average expenditure per patient was R$57,043.00 and the average annual expenditure per transplant ranged from R$59,267.00 in 2001 to R$70,561.00 in 2011. The average expenditure on other hospital admissions varied from R$ 816.07 in 2001 to R$2,248.18 in 2011, while the median ranged from R$333.88 to R$860.20. The results showed that the probability of surviving, hospital expenses, hospitalization rates and the number of days of inpatient care are higher for the first posttransplant year. As a result, our estimates show higher expenditures per life year gained in the first posttransplant year compared to the subsequent periods. The shorter hospital expenditures per life year gained in the first posttransplant year was R$3,409.00 in the 2002 cohort, reaching a value of R$8,752.00 in the 2011 cohort.